Mathematical analysis of replication by cash flow matching - Jan Natolski; Ralf Werner (Risks, 2017)
The replicating portfolio approach is a well-established approach carried out by many life insurance companies within their Solvency II framework for the computation of risk capital. In this note we elaborate on one specific formulation of a replicating portfolio problem. In contrast to the two most popular replication approaches, it does not yield an analytic solution (if, at all, a solution exists and is unique). Further although convex, the objective function seems to be non-smooth and hence a numerical solution might thus be much more demanding than for the two most popular formulations. Especially for the second reason, this formulation did not (yet) receive much attention in practical applications, in contrast to the other two formulations. In the following, we will demonstrate that the (potential) non-smoothness can be avoided due to an equivalent reformulation as a linear second order cone program (SOCP). This allows for a numerical solution by efficient second order methods like interior point methods or similar. We also show that - under weak assumptions - existence and uniqueness of the optimal solution can be guaranteed. We additionally prove that - under a further similarly weak condition - the fair value of the replicating portfolio equals the fair value of liabilities. Based on these insights, we argue that this unloved stepmother child within the replication problem family indeed represents an equally good formulation for practical purposes.
Keywords: 330; life insurance; replicating portfolio; market consistent valuation; cash flow matching; fair value; stochastic Fermat-Torricelli problem